Legal Protection for Medical Laboratories Concerning Risk-Based Business Licensing Standards and the Fulfillment of Clinical Pathology Specialist - Etik Nunuk Setyorini; Mokhamad Khoirul Huda; Andika Persada Putra (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
Medical laboratories play a crucial role in the healthcare system but often face regulatory challenges, particularly in the context of licensing. The amendment to the Ministry of Health Regulation on the Standards of Business Activities and Risk-Based Licensing in the Health Sector, which requires Clinical Pathology Specialists (DSPK) as the responsible physician, replacing general practitioners, has created difficulties for medical laboratory operators. The main issue is the uneven distribution of DSPK across Indonesia, which impacts the operation of medical laboratories. This research aims to analyze the legal protection of medical laboratories concerning the fulfillment of risk-based business licensing standards, particularly regarding the requirement for DSPK. The research employs a normative juridical method by examining relevant laws, government regulations, and judicial decisions. The results indicate that in the formulation of regulation, the legislative rationale must consider philosophical, sociological, and juridical aspects. However, the sociological aspects is not fully addressed due to the uneven distribution of DSPK, rendering the regulation ineffective at the national level. This issue hampers public access to quality laboratory services. Therefore, legal protection is needed to ensure that national health standards are achieved without creating disparities in access to healthcare services across different regions.